2003
DOI: 10.1111/j.0042-9007.2003.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal genotyping of RHD and SRY using maternal blood

Abstract: This method is not suitable for routine analysis because of the lack of a positive control for RHD-negative female fetuses and a decrease in PCR sensitivity when performing duplex PCR. Fetal DNA in maternal plasma is better preserved when the blood sample is kept cool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 30 publications
2
28
2
8
Order By: Relevance
“…Similarly, a lack of consistency in the handling and reporting of replicates will limit the generalisability of study findings. Randen et al [34] reported a decrease in the number of false results and an increase in accuracy when only one positive result, rather than all replicate outcomes, were considered. Reported test performance is, therefore, laboratory specific and might not be replicated in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, a lack of consistency in the handling and reporting of replicates will limit the generalisability of study findings. Randen et al [34] reported a decrease in the number of false results and an increase in accuracy when only one positive result, rather than all replicate outcomes, were considered. Reported test performance is, therefore, laboratory specific and might not be replicated in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…There was no consistency in the type of control used. Y-linked markers were used in two studies but these are unable to provide a positive control for female fetuses [9,34]. Insertion deletion polymorphisms (IDPs) were used in four studies; these are sex independent and appear reasonably robust [14,16,31,36].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…amniocentesis or collection of fetal blood, provided that the validity of the non-invasive diagnosis is proven. The reliability of non-invasive RHD typing with real-time PCR was investigated in large studies during the past decade [2,3,4,5,6,7,8,9,10,11,12,13]. The majority of the studies focused on screening of RHD -negative pregnant women to assess the need for anti-D-prophylaxis during pregnancy and collected samples after the 20th week of gestation [14,15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%